A bibliometric analysis of light chain amyloidosis from 2005 to 2024: research trends and hot spots - Liu, Xiangdong; Wang, Junyan; Li, Yingmin; Shi, Weibo; Zhang, Xiaojing; Li, Shujin; Cong, Bin (Frontiers in Medicine, 2024)
Light chain (AL) amyloidosis stands as the most prevalent subtype of systemic amyloidosis, encompassing a group of rare diseases. Here, we evaluated the scientific landscape of AL amyloidosis to investigate research trends and identify hotspots within the field. Relevant studies on AL amyloidosis published over the past two decades were retrieved from the Web of Science Core Collection. A total of 2864 publications between 2005 and 2024 were subjected to bibliometric analyses, leveraging tools including CiteSpace, VOSviewer, RStudio and MS Excel to analyze and visualize the annual publication trend, co-occurrence patterns, collaborative networks among countries, organizations, and authors. Burst keywords and references were also examined to obtain the research history, and emerging hotspots. The most productive journal is Amyloid-Journal of Protein Folding Disorders. The United States, along with several developed nations, emerges as a dominant force in international AL amyloidosis research. "AL amyloidosis" and "cardiacamyloidosis" were the primary hotspots over the past two decades, and "Biomarkers", "Cardiac amyloidosis", and "treatment" would be future trends. This field has been attracted increasingly attention in recent few years and is undergoing a rapid developmental stage.